Character Education Values in the Bugis Traditional Game of Mappasajang: An Islamic Perspective - Sarifa Suhra (Ulumuna, 2023)
This study examines the traditional Bugis mappasajang game and analyses the intersection of traditional values in that game with those of Islamic traditions. Based on the empirical research in Toro Village, Bone, South Sulawesi, the study employed observation and interview to collect the data. This study found that despite the negative impacts of game, like other games that often take excessive time and neglects daily routines amongts children or youth, the study shows that noble characters are inherently present in the traditional game. The player of mappasajang can learn how to make balance, create resilience, and establish cooperation, unity and creativity since all these characters and skills are badly needed to play the game successfully. In addition to sharpen motoric skills, unlike online games, the traditional game also helps to nurture one’s personality in dealing with others and strengthen social bond and community cohesion. This is relevant to the principle of traditional game or sport promoted by Islam.